Feasibility of Silica Loaded NBR as Lining Material for Impactive Gripper. (2016) - Thomas, O.; Namboothiri, V.N.N.; Joseph, Rani
Abstract: The effect of silica loading on the static frictional coefficient of nitrile rubber when paired with different types of papers is investigated. The influence of silica loading on the mechanical properties of nitrile rubber and its changes due to natural ageing is also examined. The objective of the study is to generate data for assessing the suitability of NBR as a lining material for impactive grippers. It is observed that the properties of NBR including frictional coefficient can be modified by varying the amount of silica. The static co-efficient of friction with most of the papers is highest at around 55 phr of silica. The properties like hardness, tear strength and resistance to oil increase with the amount of silica content while swelling index decrease with silica loading and the abrasion index peaks around 55 phr. The change in the mechanical properties due to natural ageing varies, though marginally.